he Influence of Brand Image and Price on the Decision to Purchase an Avanza Car at PT. Hadji Kalla Daya Makassar Branch - Nurul Syam - Syam; Dg. Maklassa; Nasrullah , Nasrullah (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this research is a type of quantitative research with the aim of finding out how much influence brand image and price have on the decision to purchase an Avanza car at PT. Hadji Kalla Daya Makassar Branch. The population in this study was 80 people with a sample of 67 respondents using a Non Probability Sampling sampling technique with a sampling technique, namely Incidental Sampling. The types and sources of data used are primary data and secondary data with questionnaire data collection and documentation. Meanwhile, the data analysis methods used are validity test, reliability test, normality test, and partial hypothesis test (t test). The results of this research show that the brand image and price variables simultaneously have a positive and significant effect on the decision to purchase an Avanza car at PT. Hadji Kalla Daya Makassar Branch. Brand image and price variables influence purchasing decisions. Based on the results of the t test, the Brand Image Significance Value of 0.001 is smaller than the specified significance value of 0.05, so based on this decision making, there is an influence of brand image in purchasing decisions. Meanwhile, the price significance value of 0.001 is smaller than the significance value set at 0.05, so there is an influence of price in purchasing decisions.